Sterowanie rozwojem pod presją funkcji dominującej a konkurencyjność regionu - Meyer, Beata (Development Steering Under the Dominant Function Pressure VS. the Region's Competitiveness, 2005)
Seasonal variability of functioning of tourist reception regions determines the work of the local autonomy, which objectives and tasks varies during the year. The steering of the region aim is to establish such conditions, in which the participants of the economic and social life will handle in a way which supports achieving the defined level of regional development and economical profile of the region. Local autonomy's interest is to create suitable conditions and to incentive the activities which support the defined local aim. The long-term target is to get the competitive advantage over the similar regions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 40-45